Cybersecurity Skill Gap in India - Tripathi, Abhishek (Journal of Advanced Research in Electronics Engineering and Technology; Vol 12 No 1&2 (2025): Journal of Advanced Research in Electronics Engineering and Technology, 2025)
Cybersecurity is a challenge that the world is dealing with, and at the pace and scale at which the adversaries are advancing, the cybersecurity skill gap is the biggest menace the enterprises and the countries are facing. India, however, is in a unique position to find “Aapda Mein Avsar” (opportunity in adversity) with its young and educated workforce. India is at the curb to solve this problem for both itself and the world. This review examines the consequence of the lack of appropriate cybersecurity education and workforce readiness to encash these opportunities by identifying the gaps and addressing them with the possible solutions. This review paper scours through the existing literature looking for the gaps in the existing structure and explores the strategies to mitigate them. It also reviews various approaches to bridge this gap through industry collaboration, gamification and inclusivity.